2018
DOI: 10.1101/450668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular polarity asymmetrically functionalizes pathogen recognition receptor-mediated intrinsic immune response in human intestinal epithelium cells

Abstract: 50Intestinal epithelial cells (IECs) act as a physical barrier separating the 51 commensal-containing intestinal tract from the sterile interior. These cells have 52 found a complex balance allowing them to be prepared for pathogen attacks 53 while still tolerating the presence of bacteria/viral stimuli present in the lumen 54 of the gut. Using primary human IECs, we probed the mechanisms, which allow 55 for such a tolerance. We discovered that viral infection emanating from the 56 basolateral side of IECs eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…We found that $10% of the cells are infected in a human-colon-derived organoid, leading to a modest but significant increase in viral genome copy number (Figure 4F) and de novo infectious virus particles (Figure 4J) over time. This modest replication of SARS-CoV-2 is explained by the fact that (1) only a small fraction of the cells are infected by SARS-CoV-2, and (2) as shown in this work, IFNs are potent inhibitors of SARS-CoV-2 replication (Figures 2 and 3), and organoids are highly immunoresponsive upon viral infection (Stanifer et al, 2020) (Figure 4G). Our findings are in agreement with recent work from Lamers et al showing that infection of human intestinal organoids by SARS-CoV-2 induces a strong immune response characterized by a strong expression of ISGs (Lamers et al, 2020).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…We found that $10% of the cells are infected in a human-colon-derived organoid, leading to a modest but significant increase in viral genome copy number (Figure 4F) and de novo infectious virus particles (Figure 4J) over time. This modest replication of SARS-CoV-2 is explained by the fact that (1) only a small fraction of the cells are infected by SARS-CoV-2, and (2) as shown in this work, IFNs are potent inhibitors of SARS-CoV-2 replication (Figures 2 and 3), and organoids are highly immunoresponsive upon viral infection (Stanifer et al, 2020) (Figure 4G). Our findings are in agreement with recent work from Lamers et al showing that infection of human intestinal organoids by SARS-CoV-2 induces a strong immune response characterized by a strong expression of ISGs (Lamers et al, 2020).…”
Section: Discussionsupporting
confidence: 51%
“…This highlights that host-pathogen interaction should be considered in a tissue-specific manner, as different cellular responses and viral countermeasures might be established among the lung, gut, and other organs. Interestingly, in human colon organoids, we observed that only type III IFN is made upon SARS-CoV-2 infection, although human intestinal organoids are capable of making both type I and III IFN upon enteric virus infection (Pervolaraki et al, 2018;Stanifer et al, 2020). The lack of type I induction could be due to a kinetic delay of type I IFN production compared to type III IFN but this will need to be carefully addressed in further experiments.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These differences likely affect the responsiveness of the epithelium to the microbiota and result in differences in microbiota-mediated tonic signaling between the mouse and human intestine (Hamonic et al, 2018;Price et al, 2018). Indeed, studies in mice have shown that TLR stimulation of enterocytes apically versus basolaterally results in different responses (Lee et al, 2006;Stanifer et al, 2019). Moreover, systemic flagellin, but not LPS, protected mice against enteric rotavirus in a TLR5-and NLR family CARD domain-containing 4 (NLRC4)dependent manner (Uchiyama et al, 2014).…”
Section: Mammalian Enteric Studiesmentioning
confidence: 99%
“…Moreover, systemic flagellin, but not LPS, protected mice against enteric rotavirus in a TLR5-and NLR family CARD domain-containing 4 (NLRC4)dependent manner (Uchiyama et al, 2014). This is likely due to the different immune responses as is seen for apical versus basolateral stimulation of TLRs on intestinal epithelial cells (IECs) (Lee et al, 2006;Stanifer et al, 2019). For example, TLR5 is located on the basolateral side of IECs, which would make it only responsive to systemic flagellin (Rhee et al, 2005).…”
Section: Mammalian Enteric Studiesmentioning
confidence: 99%